Asian soybean rust control efficacy calculated with AUDPC and with final severity data - Reis,Erlei Melo (2022)
ABSTRACT Data from experiments conducted in the field during four growing seasons aiming at the chemical control of soybean rust caused by Phakopsora pachyrhizi, the control values calculated for the area under the disease progress curve (AUDPC) were compared with those of the final severity. Data were analyzed according to a factorial experiment: (i) treatments with fungicides and (ii) rust control. Out of 70 treatments, the control was always lower when calculated with the AUDPC than with the final severity. In the general means for four growing seasons, the AUDPC control was of 48.5 (range 36 to 65%) and for calculation with the final severity 43.25% (range 29 to 66%). It can be concluded that, in the case of soybean rust, the control calculation shows advantage when performed with final severity data.